INTEGRATING MOBILE PHONES FOR EFFECTIVE EFL LEARNING (Konferensiyalar | Conferences, 2024)
The article explores how using mobile phones in English as a foreign language (EFL) classrooms can shift the teacher's role from instructor to facilitator. It highlights the importance of student-teacher interaction and collaborative learning, where students work together using technology to share ideas, thoughts, and information effectively.